Analisis Sistem Pengupahan “Bawon” pada Pertanian Padi (Studi Kasus pada Petani di Desa Gambar Kecamatan Wonodadi Kabupaten Blitar) - Dwi Wahyuni (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2016)
As an agricultural country, agricultural sector plays an important role in the Indonesia economic life, especially in rural areas. Farm laborers as one component of the agricultural sector, have a considerable contribution in determining the success of this sector. But there are unique facts occur in Blitar Regency, one of which happened in Gambar, Wonodadi District, Blitar Regency related to wage system called "bawon" system when harvesting rice. The "bawon" system is a profit-sharing system given to farm laborers working on a patch of land from the start of the rice planting to the harvest, whose share of income depends on the area of cultivated land and the number of harvest yields. The purpose of this research is to analyze the Bawon system that is still done between the landowners and farm workers in the Village Picture District Wonodadi Blitar. This research used descriptive explorative statistical approach to provide an in-depth description of the Bawon system. To analyze the data obtained, the researchers used Component Analysis (Componential Analysis) technique, in which the researcher attempted to sort and illustrate the differences found in the data obtained from the field. The results showed that farm laborers earn 20% of the total grain yield when finished harvesting the crops, while 80% is the land owner's.